ANALISIS FUNGSI DAN PERANAN KURIKULUM DALAM IMPLEMENTASI KEBIJAKAN SEKOLAH: STUDI KASUS DI MIS AL-FATTAH MOJOLANGU KOTA MALANG - Ikhwanul Habib; Taqiyuddin Kabalmay; Sintya Rahmadewi (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
This study aims to analyze the functions and roles of the curriculum at MI Al-Fattah, which emphasizes the holistic development of students. The background of this research is based on the importance of the curriculum as the foundation of learning that supports self-adjustment, social integration, differentiation, preparation for further education, freedom to choose interests, and a diagnostic function for developing students’ potential. This research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The analysis technique uses the Miles and Huberman model, which includes the stages of data reduction, data presentation, as well as conclusion drawing and verification. The results show that the curriculum at MI Al-Fattah operates optimally in carrying out its six main functions, which are relevant to the goals of Islamic elementary education. The implementation of the curriculum supports the formation of adaptive, critical students who are ready to continue their education to higher levels. This study recommends strengthening the role of teachers, synergy with parents, and learning innovations to further optimize the functions and roles of the curriculum in the future.